A cautious balance – explaining India's approach toward Afghanistan's peace process. Issue 2 (3rd May 2020) - Paliwal, Avinash
ABSTRACT: The US president Donald Trump pitched India's participation as being central to his Afghanistan policy in 2017. Yet, as the US has sought a negotiated settlement with the Afghan Taliban, there is little clarity on how India seeks to deal with its increasing isolation in Afghanistan. This article focuses on India's response toward the peace talks of 2015 and 2018/19 and investigates why its position changed. In 2015, New Delhi viewed Kabul's outreach to Pakistan as a "tilt" harmful to India's strategic interests; in 2018/19, India sought international support for Kabul to enter dialog without preconditions. The article argues that India seeks to ensure an ongoing strategic balance between Afghanistan and Pakistan. The source of such contrasting responses to the two peace talks, then, lies in India's perception of and confidence in the US' approach toward Afghanistan, and the changing landscape of Afghan domestic politics.